Microbiology - Pelczar, Michael J. (Michael Joseph) (New York : McGraw Hill Education, 1986)
This fifth edition of MICROBIOLOGY retains many of the features that have proved successful in the first four editions, particularly the balance between fundamental or basic microbiology and applied microbiology. This approach emphasizes the importance of integrating new knowledge gained through basic research with applied research and development programs.
Part One. Introduction to microbiology -- Part Two. Microorganisms - bacteria -- Part Three. Microbial physiology and genetics -- Part Four. The world of bacteria -- Part Five. Microorganism-fungi, algae, protozoa and viruses -- Part Six. Control of microorganism -- Part Seven. Environmental and industrial microbiology -- Part Eight. Microorganism and disease.
Includes index.
Keywords: MICROBIOLOGY